2014
DOI: 10.1007/s00203-014-1015-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the biosynthesis of antibacterial cyclic dipeptides in Nocardiopsis alba

Abstract: Nocardiopsis alba is frequently isolated from environment and has recently been suggested as a casual symbiotic actinobacterium of diverse invertebrates. Using activity-guided fractionation, we purified two antibacterial cyclic dipeptides, cyclo(ΔPhe-ΔLeu) (albonoursin) and cyclo(ΔmTyr-ΔLeu), from a culture of Nocardiopsis alba ATCC BAA-2165. Analysis of N. alba genome revealed genetic information similar to albonoursin biosynthetic gene cluster, albABC. An albABC gene deletion mutant of N. alba was generated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…For example, HT88 extracts showed antimicrobial activity against test bacteria which is in accordance with our findings; antimicrobial activity of KUMS-C2. Two antibacterial cyclic dipeptides, cyclo(ΔPhe-ΔLeu) (albonoursin) and cyclo(ΔmTyr-ΔLeu), reported from this strain [ 78 ] which is in line with our antibacterial data for the closest isolate. KUMS-C4 was closely related to the Streptomyces durmitorensis strain.…”
Section: Discussionsupporting
confidence: 87%
“…For example, HT88 extracts showed antimicrobial activity against test bacteria which is in accordance with our findings; antimicrobial activity of KUMS-C2. Two antibacterial cyclic dipeptides, cyclo(ΔPhe-ΔLeu) (albonoursin) and cyclo(ΔmTyr-ΔLeu), reported from this strain [ 78 ] which is in line with our antibacterial data for the closest isolate. KUMS-C4 was closely related to the Streptomyces durmitorensis strain.…”
Section: Discussionsupporting
confidence: 87%
“…Another group mainly synthesizes a cFX compound, as AlbC; it contains CDPSs 62, 66, 67, four previously characterized members (Gondry et al, 2009 ; Giessen et al, 2013b ; Li et al, 2014 ; Jacques et al, 2015 ) and a recently identified member that produces mainly cFY (Brockmeyer and Li, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Assembly of the DKP backbone through condensation of two amino acids can be catalyzed by non-ribosomal peptide synthetases (NRPSs) or cyclodipeptide synthases (CDPSs) (Borgman et al 2019;Canu et al 2020). These cyclodipeptides (CDPs) can undergo several tailoring modifications such as methylation, hydroxylation, prenylation, dimerization/coupling, and dehydrogenation, which can enhance their biological and pharmacological activities (Borgman et al 2019;Canu et al 2020;Giessen and Marahiel 2014;Li et al 2014;Yu et al 2018).…”
Section: Introductionmentioning
confidence: 99%